Experimental and numerical investigations of the jetting regime. Issue 1 (1st January 2023) - Tanase, Nicoleta-Octavia; Rasuceanu, Ioana; Balan, Corneliu
Abstract: In this paper we highlight the first stages of liquid injection through a capillary nozzle prior to the jet formation regime. We emphasize the asymmetry of water-air interface at the beginning of the injection of liquid and the axial symmetry which follows when the jet is fully formed. Numerical simulations are performed in order to estimate the relaxation of the velocity distribution of the liquid as it leaves the capillary nozzle. The plug flow condition for low-viscosity liquid jets is investigated in relation with the parabolic velocity distribution in the nozzle. The numerical data is also used to characterize the flow during the drop formation and pinch-off, both driven by the action of surface tension.